Penerapan Terapi Menggambar terhadap Perubahan Tingkat Halusinasi Pendengaran - Yuliana, Yuliana; Mulyani, Sri (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to determine the application of drawing therapy to changes in hallucination levels in clients with auditory hallucinations in the Gama Inpatient Ward, Jambi Province Regional Mental Hospital. Data collection was carried out through observation, interviews, documentation, and using instruments in the form of an AHRS questionnaire and an observation sheet for signs and symptoms of hallucinations. The results of this study found that there was a decrease in the score of signs and symptoms of hallucinations after the implementation of nursing care, namely drawing therapy, in patients in the Gama Inpatient Ward, Jambi Province Regional Mental Hospital.